Multifunctional, Fluorene-Based Modulator of Cholinergic and GABAergic Neurotransmission as a Novel Drug Candidate for Palliative Treatment of Alzheimer's Disease - Panek, Dawid; Pasieka, Anna; Jończyk, Jakub; Gawlińska, Milena; Zaręba, Paula; Siwek, Agata; Wolak, Małgorzata; Mordyl, Barbara; Głuch-Lutwin, Monika; Latacz, Gniewomir; Brazzolotto, Xavier; Chantegreil, Fabien; et al. (Angewandte Chemie (International ed. in English), 2025)
Alzheimer's disease (AD) is a neurodegenerative disorder characterized by memory loss and behavioral and psychological symptoms of dementia (BPSD). Given that cholinergic neurons are predominantly affected in AD, current treatments primarily aim to enhance cholinergic neurotransmission. However, imbalances in other neurotransmitters, such as γ-aminobutyric acid (GABA), also contribute to AD symptomatology. In the presented research, using a combination of crystallography and computational methods we developed compound 6 as a dual modulator of GABAergic and cholinergic neurotransmission systems. Compound 6 demonstrated inhibition of BuChE (IC50=0.21 μM) and GABA transporter 1 (IC50=10.96 μM) and 3 (IC50=7.76 μM), along with a favorable drug-likeness profile. Subsequent in vivo studies revealed the effectiveness of 6 in enhancing memory retention and alleviating anxiety and depression symptoms in animal models, while also proving safe and bioavailable for oral administration. The innovative multi-target-directed ligand 6 offers a new approach to treating cognitive deficits and BPSD in AD.
Keywords: proteiny přenášející GABA přes plazmatickou membránu; fluoreny; Humans; butyrylcholinesterase; GABA Plasma Membrane Transport Proteins; lidé; Alzheimer Disease; zvířata; Alzheimerova nemoc; myši; molekulární struktura; cholinesterasové inhibitory; Mice; Molecular Structure; Synaptic Transmission; nervový přenos; butyrylcholinesterasa; Acetylcholinesterase; Fluorenes; gamma-Aminobutyric Acid; Alzheimer's disease; inhibitors; GABA; Animals; multitarget drugs; Butyrylcholinesterase; GABA transporters; acetylcholinesterasa; Cholinesterase Inhibitors